ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN BERBASIS EFIKASI DIRI DAN BUDAYA ORGANISASI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Kartini, Tini; Yuningsih, Erni; Nisa, Nida Khoerun (Universitas Nusa Cendana, 2024)
The research objectives are to examine the influence of self-efficacy and organizational culture on organizational citizenship behavior (OCB) with organizational commitment as an intervening variable. A sample of 100 respondents used the purposive sampling method. Data research methods use descriptive, verification, and path analysis. This study found that self-efficacy has a direct positive and significant effect on organizational commitment, organizational culture has a direct positive and significant impact on organizational commitment, organizational commitment has a direct positive and significant effect on employee OCB, self-efficacy has a direct positive and significant impact on OCB employees, organizational culture has a direct positive and significant effect on employee OCB, organizational commitment is able to mediate the influence of self-efficacy on employee OCB, and organizational commitment is able to mediate the impact of organizational culture on employee OCB. Keywords: Self Efficacy; Organizational Culture; Organizational Citizenship Behavior; Organizational Commitment